Analysis of Symbols in Kaili Customary Sanctions - Judana; Syamsuddin (Institut Agama Islam Negeri Palopo, 2025)
This study aims to determine the form of symbols in kaili customary sanctions and describe the meaning in the form of symbols in kaili customary sanctions. Kaili customary sanctions do not only function as punishments but as a holistic process that aims to restore balance and harmony in the community both socially and spiritually. The method used is a qualitative descriptive method. The results of this study show that Symbols such as goats and buffaloes represent different levels of sacrifice and purification, adjusted for the weight of the offense. Goats for general cleansing and expressions of gratitude, while buffalo for serious offenses that require total purification and a deep restoration of honor. Guma (machete) symbolizes the firmness of customary law and the power to break the negative bonds caused by violations. Traditional plates, white ceramic bowls, and trays function as symbolic containers that represent agreement, purity of intention, and togetherness in the process of solving problems, as well as being a place to hand over fines or offerings. Meanwhile, the white cloth emphasizes aspects of purity, peace, and sincere intentions to start a new chapter. Finally, the dowry (customary fine) is a symbol of accountability and compensation, which affirms the recognition of wrongdoing and the commitment to restore the dignity or loss that has occurred.